2022
DOI: 10.1039/d2dt00335j
|View full text |Cite
|
Sign up to set email alerts
|

MicroED characterization of a robust cationic σ-alkane complex stabilized by the [B(3,5-(SF5)2C6H3)4] anion, via on-grid solid/gas single-crystal to single-crystal reactivity

Abstract: The thermally and chemically robust σ-alkane complex [Rh(Cy2PCH2CH2PCy2)(norborane)][B(3,5-(SF5)2C6H3)4] is characterized by micro-electron diffraction using on-grid single-crystal to single-crystal reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…This is similar to the formation of the cyclotrimerization product 7 in propyne hydrogenation using 1. The 31 P{ 1 H} SSNMR of 11 shows very broad signals at δ 91.4 and ∼δ 71 77 (fwhm ∼2100 Hz, compared with 10 fwhm = 500 Hz) that indicate the formation of an amorphous phase, and consistent with this, SEM analysis of material pre-and post-catalysis shows that significant degradation of the crystal has occurred. Collectively, these data confirm how careful choice of the phosphine substituents is necessary if long catalyst lifetimes are to be maintained, 39 as evident by the fact the t Bu groups in 1 promote the formation of Rh(III) hydride 4 in solid-state.…”
Section: Changing the Smom Catalyst To [Rh-(cy 2 Pch 2 Ch 2 Pcy 2 )(C...supporting
confidence: 53%
“…This is similar to the formation of the cyclotrimerization product 7 in propyne hydrogenation using 1. The 31 P{ 1 H} SSNMR of 11 shows very broad signals at δ 91.4 and ∼δ 71 77 (fwhm ∼2100 Hz, compared with 10 fwhm = 500 Hz) that indicate the formation of an amorphous phase, and consistent with this, SEM analysis of material pre-and post-catalysis shows that significant degradation of the crystal has occurred. Collectively, these data confirm how careful choice of the phosphine substituents is necessary if long catalyst lifetimes are to be maintained, 39 as evident by the fact the t Bu groups in 1 promote the formation of Rh(III) hydride 4 in solid-state.…”
Section: Changing the Smom Catalyst To [Rh-(cy 2 Pch 2 Ch 2 Pcy 2 )(C...supporting
confidence: 53%
“…In contrast to other MOCHA materials with an extended metal chalcogenide core, MicroED has revealed that the synthesized carborane-structured MOCHAs consist of an unprecedented zero-dimensional Cu 4 Se 4 cluster that is representative of the smallest building block of bulk CuSe materials. This work therefore further establishes the utility of MicroED for hybrid material structure elucidation when reaching the limitations of more traditional structural determination methods. This study furthermore highlights how the use of bulky, organomimetic, boron cluster ligands can lead to the formation of hybrid materials with unique structures and properties. , , …”
Section: Discussionmentioning
confidence: 64%
“…16 All three measures were consistent with the greater stability of Previously, non-covalent interactions (NCI) plots 22 have highlighted broad areas of dispersive stabilisation between the alkane ligand and the neighbouring [BAr F 4]anions in these -alkane complexes. 11,13,14,17,18 In addition, more localised disk-like features have suggested the presence of C-HF contacts and we have commented on the potential role of such interactions in conferring stability in the solid state. 17 exhibit each end of the range of stabilities seen to date in crystallographically characterised -alkane complexes in the solid state.…”
Section: Faraday Discussion Accepted Manuscriptmentioning
confidence: 90%